The Effect of Service Quality on Customer Loyalty Mediated by Customer Satisfaction in Tourism Villages in Badung Regency - I Gusti Ngurah Surahman; Putu Ngurah Suyatna Yasa; Ni Made Wahyuni (Universitas Warmadewa, 2020)
The aims of this research was to determine the effect of service quality with customer loyalty. And customer satisfaction as a mediator between the relationship of service quality with customer loyalty. This research was collected data from 100 respondents who were customers who visited the Tourism Village in Badung Regency. The data were analyzed using structural equation modeling with partial least square approach. The results indicate an insignificant direct effect of service quality on customer loyalty. Significant direct influence on service quality with customer satisfaction, and customer satisfaction with customer loyalty. Furthermore, the results show an indirect effect between service quality and customer loyalty, which is mediated by customer satisfaction. The findings was empirically indicate that service quality has a negative effect on customer satisfaction. And customer satisfaction has a full mediating effect, customer satisfaction is important explaining the quality of service to drive customer loyalty. Based on the results it can be concluded that this research offers empirical evidence of the relationship of service quality, customer satisfaction and customer loyalty. This research makes a theoretical contribution to clarifying the high level of service quality increasing customer loyalty through customer satisfaction.